2021
DOI: 10.3390/soilsystems5030038
|View full text |Cite
|
Sign up to set email alerts
|

No Tillage Improved Soil Pore Space Indices under Cover Crop and Crop Rotation

Abstract: Assessment of the effects of crop management practices on soil physical properties is largely limited to soil moisture content, air content or bulk density, which can take considerable time to change. However, soil pore space indices evolve rapidly and could quickly detect changes in soil properties resulting from crop management practices, but they are not often measured. The objective of this study was to investigate how soil pore space indices—relative gas diffusion coefficient (Ds/Do) and pore tortuosity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…However, when adopting non-conservationist tillage systems (CT) an increase in soil density was observed, both in the 0-0.10 m and 0.10-0.20 m. This increase in soil density reaches the order of 13.6% more in relation to direct planting in the 0-0.10 m layer and 15% in relation to NT in the layer between 0.10 and 0.20 m, both using Millet as a previous crop (Table 1). This observation agrees with other research studies (Ouda et al, 2018;Panday & Nkongolo, 2021).…”
Section: Soil Densitysupporting
confidence: 94%
“…However, when adopting non-conservationist tillage systems (CT) an increase in soil density was observed, both in the 0-0.10 m and 0.10-0.20 m. This increase in soil density reaches the order of 13.6% more in relation to direct planting in the 0-0.10 m layer and 15% in relation to NT in the layer between 0.10 and 0.20 m, both using Millet as a previous crop (Table 1). This observation agrees with other research studies (Ouda et al, 2018;Panday & Nkongolo, 2021).…”
Section: Soil Densitysupporting
confidence: 94%
“…The soil structure quality at Dzingahe was found to be better than that at Tshivhilwi when compared across the tillage systems. The results suggested that the tillage systems did not exclusively alter the soil structure but other practices such as cropping systems and residue management could have contributed to the changes [11,28,29]. It was observed that the tillage systems were not practised in the same way in these two locations and that the duration of NT was also different, with a gap of more than 30 years.…”
Section: Discussionmentioning
confidence: 95%
“…It is well documented in the literature that high soil density has greater proportion of micropores [2]. However, the cultivation of diferent species of cover crops, with diferent root arrangements, explores the soil profle at diferent depths, contributing to soil aggregation and promoting greater pore connectivity, resulting in an increase in total porosity [29,30].…”
Section: Discussionmentioning
confidence: 99%